Проблеми формування та реалізації людського капіталу як чинника сталого розвитку в економіці України - Бакіна, Тетяна Володимирівна; Бакина, Татьяна Владимировна; Bakina, Tetiana (Вид-во Мелітопольська типографія «Люкс», 2013)
UK: У статті досліджується державна політика України, її об'єкти і проблеми, пов'язані з розвитком соціальної сфери, з формуванням і використанням людського капіталу. EN: Creation of conditions for economic growth in the post-industrial era encounters in Ukraine on a number of serious obstacles. First, in the last decade of development of the economy of Ukraine passes in conditions of the worsening of the demographic situation. The projected change in the population dynamics and structure of the population could become a factor reluctant to sustainable development of the economy of Ukraine and the deteriorating social situation. The most important ways of increasing the quality of the population could be the development of the spheres of health and education. But the state health care system in Ukraine in poor condition. Introduced in Ukraine, the system of medical insurance has not produced the anticipated results Not less important is the direction of improving the quality of population in the conditions of postindustrial transformation is the development of the education system, and, first of all, higher education. But Ukrainian education, as well as the Ukrainian science, is experiencing a multitude of problems. One of them is formed in it low even by Ukrainian standards, the level of income and generally insufficient state financing of Ukrainian education. The Ukrainian government, aware of the urgent need to tackle the problems of the social sphere, taking steps to find a way out of them. But today, social policy of the Ukrainian state does not focus on the person, the development of human capital. The author defended the position, which is that in the era of post-industrialism human development is not only desirable, but a necessity and competitive advantage in the international arena.
Keywords: сталий розвиток; людський капітал; освіта; охорона здоров'я; економіка України; державна політика України; обє'кти державної політики України; соціальна сфера